Analysis of Collective Memory, Identity, and Narrative in Mourid Barghouti's Novel Ra'aitu Ramallah - Perdana, Dyah Adila Perdana (Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2025)
This study aims to analyze Mourid Barghouti’s memories in his memoir Ra’aitu Ramallah using a basic interpretive qualitative approach, drawing on Maurice Halbwachs’ theory of collective memory, Paul Ricoeur’s narrative theory, and Antonio Gramsci’s concept of cultural hegemony. The research focuses on how the memoir represents the suffering of Palestinians after the 1967 Naksa through the narration of personal memories that simultaneously reflect the collective memory of the Palestinian people. The study is based on an in-depth reading of the text and a review of relevant previous literature. The findings reveal that Barghouti’s recollections address crucial themes such as war, death, massacres, terrorism, occupation, borders, poverty, irony, and the Nakba. These memories do not merely depict individual experiences but articulate a shared memory aimed at recovering Palestinian national identity. The study also shows that Barghouti’s selection of memories is intentional, serving to shape his Palestinian identity and to employ the memoir as a form of counter-cultural hegemony intended to expose Israeli occupation and reinforce a narrative of resistance within collective consciousness. Thus, Ra’aitu Ramallah becomes a symbolic space of struggle through literature, where memory and narrative function as tools to resist forgetting and cultural dispossession.